1998
DOI: 10.1002/hep.510270630
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin inhibits protein synthesis and cell proliferation induced by mitogenic factors in primary human and rat hepatocytes

Abstract: Ribavirin, a guanosine analog, used in combination with interferon ␣ (IFN-␣) in the treatment of chronic hepatitis induced by hepatitis C virus (HCV) infection, has been shown to improve liver histology and to decrease transaminases even when administered alone. We analyzed the direct effects of ribavirin on the liver by using primary cultures of human and rat hepatocytes. Between 10 to 60 mol/L, ribavirin was found to inhibit both the synthesis and secretion of whole proteins in a time-and dosedependent fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…In accordance to our previous observations (29,37), adult rat hepatocytes stimulated with EGF 4 h after seeding and throughout culture, started to incorporate [ 3 H]thymidine between 42 and 54 h, reaching a maximum around 72 h (data not shown). In unstimulated cultures, incorporation of the tracer was very low.…”
Section: Amounts Of the Cdk Inhibitors Decrease During Development Ofsupporting
confidence: 92%
“…In accordance to our previous observations (29,37), adult rat hepatocytes stimulated with EGF 4 h after seeding and throughout culture, started to incorporate [ 3 H]thymidine between 42 and 54 h, reaching a maximum around 72 h (data not shown). In unstimulated cultures, incorporation of the tracer was very low.…”
Section: Amounts Of the Cdk Inhibitors Decrease During Development Ofsupporting
confidence: 92%
“…Ribavirin might affect signal transduction pathways by exerting nonspecific effects on cell proliferation and protein synthesis. However, the minimal ribavirin dose needed to significantly affect cell proliferation and protein synthesis was 500 M after 24 h and 60 M after 72 h in primary human hepatocytes (14).…”
Section: Discussionmentioning
confidence: 95%
“…In fact it has been demonstrated that ribavirin also inhibits protein synthesis in cultured hepatocytes [Ilyin et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%